ESOMEPRAZOLE EFFICACY IN TREATMENT OF THE INFLAMMATORY DISEASES OF THE UPPER GASTROINTESTINAL TRACT AMONG CHILDREN, SUFFERING FROM RHEUMATIC DISEASES - E.I. Alexeeva; E.G. Chistyakova; M.M. Lokhmatov; T.M. Bzarova (Вопросы современной педиатрии, 2007)
The article deals with the findings of the endoscopic examination and treatment of 80 children, suffering from rheumatic diseases. According to the esophago gastroduodenoscopy data, all the patients turned up to have inflammatory changes in the upper gastrointestinal tract of various degrees of manifestation. Moreover, only 36% of patients complained about pain in the stomach. The application of esomeprazole in the complex therapy contributed to the epithelization of erosive and ulcerous defects and dyspepsia syndrome relief among the majority of the patients. The effects of the complex therapy with esomeprazole were appraised as good among 90% of children and excellent among 9% of patients.Key words: children, rheumatic diseases, esomeprazole, gastrointestinal tract pathology.